The evaluation of pediatric-adult transition programs: What place for human flourishing? - Amélie Lanteigne; Mathilde Genest; Eric Racine (Elsevier, 2021)
Adolescents with chronic health conditions transitioning from pediatric to adult healthcare services experience a wide array of difficulties. In response, transition programs have been developed. Transition programs commonly embody goals such as autonomy and independence. However, these may not be highly valued by young adults and their families. To assess critically the current evaluation of goals and outcomes of these programs, the concept of human flourishing offers a promising alternative to concepts of quality of life. It grants that objectives pursued (e.g., health, social integration) stand to be interpreted by the agent as being valuable and coherent with their meaning-making narrative. Flourishing is also an indicator of physical and psychological health.The purpose of this paper is to review the literature on transition care to assess whether and how flourishing is addressed in the evaluation of transition programs. We carried out systematic sampling of the literature and applied a qualitative thematic content extraction strategy. Based on Ryff and Singer's integrative concept of flourishing, we examined whether six key dimensions of flourishing (self-acceptance, positive relations with others, personal growth, purpose in life, environmental mastery, and autonomy) were present in current evaluation practices. We reviewed 105 relevant papers and found that (1) 44 out of 105 articles evaluated one or more dimensions of human flourishing; (2) there was considerable variation in the assessment of these dimensions, which was sometimes minimalistic; (3) no single evaluation was based on an explicit measure of human flourishing; (4) autonomy and positive relationships were the dimensions most investigated; (5) the evaluation of transition care mostly emphasized medical aspects of health. Considering its lifelong impact, it is crucial to better understand how transition care can support the flourishing of young adults. Open-ended views on flourishing based on participatory and collaborative research designs should be explored in this context.